Bond behavior between glulam and GFRP’s using pullout direct tests - Jorge, Marco (2011)
To evaluate the bond behavior between glulam and GFRP rods using the near-surface mounted (NSM) strengthening technique, an experimental program was carried out by means of direct pullout tests. In this experimental program three variables were analyzed: the GFRP type (2 types), the GFRP location/groove size (2 types) and the bond length (Lb=30 mm, 60 mm, 120 mm and 180 mm). The instrumentation includes the loaded and free end slips, as well as the pullout force. Thirty seven specimens were tested under displacement control using a servo controlled equipment. In this work the tests are described, and the obtained results are presented and discussed.